Synthesis, Characterization, Biological Activity, and Molecular Docking Study of Some New Sulfamethoxazole Derivatives. - Athra G. Sager; Jawad Kadhim Abaies; Rusul Abdulridah Issa (مجلة بغداد للعلوم)
In this paper, new Sulfamethoxazole derivatives were studied in order to improve the treatment efficiency of this medicinal compound. Six compounds of Schiff bases were prepared via an intermediate reaction of Mannich bases. Two derivatives of thiadiazine heterocyclic compound were prepared as well. Characterization and the stereo conformations of the synthesized compounds were determined using 1H-NMR, 13C-NMR, and FT-IR techniques, in addition to elemental analysis and melting point measurements. The biological activity of the produced compounds against five types of bacteria including (Staphylococcus aureus Escherichia coli, Klebsiella pneumonia Salmonella, and Proteus) was investigated. The obtained results showed that biological activities against bacteria vary from high activity to not active. Moreover, (PyRx) software was utilized for the calculation of the binding affinity (kcal/mol) for the prepared compounds with proteins FYV (S. aureus), 4H2M (E. coli), 6P4T (Salmonella). The highest linking values with proteins were found to be (-9.4) with 4H2M   and (-7.8) with 6P4T, whereas the lowest values were found (-5.3) with FYV. On the other hand, the results revealed that amino acids located around the prepared compound, which were linked through hydrogen bonding or charged and (aryne-aryne) hydrophobic interactions were also determined.  In addition, the three dimensions’ shape, which explains the linkage way between proteins and the synthesized compounds, was stated.  By recognizing the characteristic features of amino acids, which surround these compounds, the electronic densities of the compounds were also reported.